2022
DOI: 10.1002/smll.202204283
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Polyelectrolyte Complexes from Hyaluronic Acid: Preparation and Biomedical Applications

Abstract: nanocomplexes, [8,9] nanocomposites, [10,11] nanoassemblies [12] and coacervates. [13,14] Such colloidal systems, especially when prepared from biopolymers, have been extensively investigated due to their promising properties for numerous applications in biomedical fields. [1] Their merits come from the combination of three aspects: nanomedicine, biomaterials, and green chemistry. With the emergence of nanomedicine, the use of nanocarriers can offer tremendous advantages in drug encapsulation and delivery, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 195 publications
(503 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have indicated that electrostatic interactions between zein nanoparticles and other bioactive compounds, such as quercetin and curcumin, can alter the zeta potential. , The observed zeta potential for the Zein/Que/Toc nanoparticles not only aligns with the widely accepted notion of adequate electrostatic stabilization (absolute value of the zeta potential exceeding 30 mV) but also underscores the effectiveness of incorporating α-tocopherol and quercetin into zein nanoparticles in maintaining nanoparticle stability. Additionally, the observed zeta potential of the Zein/Que/Toc nanoparticles aligns with the effectiveness of co-encapsulation in biological environments, validating the maintenance of colloidal stability …”
Section: Resultsmentioning
confidence: 56%
“…Previous studies have indicated that electrostatic interactions between zein nanoparticles and other bioactive compounds, such as quercetin and curcumin, can alter the zeta potential. , The observed zeta potential for the Zein/Que/Toc nanoparticles not only aligns with the widely accepted notion of adequate electrostatic stabilization (absolute value of the zeta potential exceeding 30 mV) but also underscores the effectiveness of incorporating α-tocopherol and quercetin into zein nanoparticles in maintaining nanoparticle stability. Additionally, the observed zeta potential of the Zein/Que/Toc nanoparticles aligns with the effectiveness of co-encapsulation in biological environments, validating the maintenance of colloidal stability …”
Section: Resultsmentioning
confidence: 56%
“…Logically, a higher absolute zeta potential at the beginning would allow a greater electrostatic repulsion to avoid such aggregation and also facilitate disaggregation during the reconstitution, which was also observed by Umerska et al [ 11 ] and Eliyahu et al [ 19 ]. Furthermore, the higher proportion of HA on the NG surface may also contribute to their better stability during freezing since HA can also have cryoprotective effects [ 1 ], e.g., by maintaining intra- and inter-molecular hydrogen bonds on the particle surface during dehydration [ 20 ]. However, after freeze-drying and reconstitution, we still observed an increase of nearly 40% in the particle size of HA/DEAE-D PEC-NGs at n−/n+ = 2.5 ( Table 1 ), which was also the most interesting n−/n+ for CUR encapsulation reported in our earlier studies [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanogels (NGs) from polyelectrolyte complexes (PECs) of hyaluronic acid (HA) have been extensively studied in recent years as biomedical platforms with high potential that have the advantages of nanomedicine, green chemistry, and the inherent properties of HA [ 1 ]. Meanwhile, thermoresponsive nanocarriers from thermosensitive polymers exhibiting a lower critical solution temperature (LCST), i.e., increased hydrophobicity upon temperature increase, have also received great attention over the last two decades for drug delivery applications owing to their interesting behaviors, notably thermo-triggered drug release which can be controlled spatiotemporally [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyelectrolytes are polymers with repeating units that have the ability to dissociate in ionizing solvents (e.g., water), yielding a highly charged main chain with either positive or negative charges . Mixing of oppositely charged polyelectrolytes in aqueous solutions can lead to rapid precipitation of amorphous solids known as polyelectrolyte complexes (PECs). The complexation between polyelectrolytes is a process mainly driven by ion pairing of charged repeat units and entropic release of bound counterions. In the past decades, PECs have emerged as an attractive category of materials due to their water processability, tunable compositions and functions, and some similarities to natural biopolymers. In particular, porous PEC materials can offer abundant surface area and internal volume for further applications in many cutting-edge areas, including but not limited to separation, catalysis, and biomedical systems. In this context, several strategies have been proposed to yield porous PEC materials with controllable porosity and morphology. One approach is aqueous phase separation (APS). In this method, a viscous solution containing oppositely charged polyelectrolytes is prepared at extreme pH conditions or in the presence of excess salt, which can break interchain ion pairs and therefore prevent polyelectrolyte complexation.…”
Section: Introductionmentioning
confidence: 99%